Lingkungan Belajar, Sikap Terhadap Profesi Guru terhadap Intensi Menjadi Guru (Studi pada Mahasiswa Fakultas Ekonomi Universitas Negeri Jakarta) - Ari Saptono; Suparno Suparno (Jurnal Ilmiah Econosains, 2016)
Abstract This study aims to determine how much direct influence of the school environment and the attitude of the teaching profession to the intention to become a teacher, Student Education at the Faculty of Economics UNJ 2015. The study was conducted by the method used is the ex post de facto with the correlational approach dngan analysis techniques lane (Path Analysis) in which the school environment directly affects the intention to become a teacher, the attitude of the teaching profession directly influence the learning outcomes of economics, as well as the school environment directly influence the attitude the teacher procession. The results showed that there is a direct influence between the variables studied based on the hypothesis. With the test model fit obtained in accordance with the hypothesis that the model empirical model of the same value by stating that the model can be accepted. Keywords: Environmental Learning, Attitudes Toward Teaching profession, intention Become a Teacher